Platelet-to-Lymphocyte Ratio as Coagulopathy Predictor in COVID-19 Patients at Margono Soekarjo Hospital - Siswandari, Wahyu; Saksana, Rachmad Aji; Indriani, Vitasari; Fuadi, Muhammad Robiul (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Coronavirus Disease 2019 (COVID-19) is a disease possibly attacking various organs and systems of the body including the coagulation system causing coagulopathy. Various laboratory biomarkers have been developed to detect coagulopathy. This research aimed to determine the correlation and ability of Platelet-to-Lymphocyte Ratio (PLR) in predicting coagulopathy when compared to D-dimer. A cross-sectional research was conducted on 1580 data of COVID-19 patients at Margono Soekarjo Hospital. The research data were then analyzed using Spearman’s correlation test to figure out the correlation between PLR and D-dimer. This research was also intended to find the PLR Cut-Off Value (COV), Odds Ratio (OR), Area Under Receiver Operating Characteristic (AUROC), and diagnostic value. Platelet-to-lymphocyte ratio value had a significant correlation with D-dimer levels (r=0.260, p=0.000). The COV of PLR was 176.61 with the OR of 2.7 (2.2-3.3 95%CI), AUROC of 0.638, sensitivity of 62%, and specificity of 62%. PLR can be used as a screening biomarker to predict the occurrence of coagulopathy in COVID-19 patients.